Nokia network security solutions handbook - Maxwell, Doug. (Rockland, Mass. : Syngress ; London : International Thomson, 2002)
The Nokia Network Security Solutions Handbook introduces readers to both the basics and the finer points of administering, configuring, and securing the Nokia IP-series hardware appliances. It introduces readers to the different hardware models and covers the features associated with each. Installation and setup are covered in detail, as well as installation and configuration of the Check Point firewall on the Nokia system. Readers will learn basic system administration, security, and monitoring before moving into advanced system administration concepts, as well as learning how to use Nokia's command line interface. Routing configurations and the different protocols involved are covered in detail, finishing off with a comprehensive discussion of the High-availability configuration that is Nokia's strength. The appendices include coverage of the UNIX basics which lie at the heart of the IPSO operating system and a review of the other packages available for Nokia systems (such as Perl and Bash). The only book dedicated to coverage of the latest Nokia hardware and software offerings, from the SOHO appliances to the enterprise-class IP700 series, with an emphasis on administering and securing these systems. Long-term market potential. The operating system referenced will be Nokia IPSO 3.4.1, which has an interface that has been specifically tailored to make upgrading to newer versions of IPSO simple and intuitive. In addition, the underlying interface is UNIX based, which has been a constant for over 30 years. Up-to-the-Minute Web-based Support. Once they have absorbed the content of the book, readers can receive up-to-the minute links, white papers, and analysis for one year at solutions@syngress.com.
Chapter 1: Overview of Nokia Hardware -- Chapter 2: Overview of Nokia IPSO Operating System -- Chapter 3: Initial Configuration -- Chapter 4: Introduction to the Voyager Web Interface -- Chapter 5: Firewall Installation -- Chapter 6: Basic System Administration -- Chapter 7: System Monitoring -- Chapter 8: Advanced System Administration -- Chapter 9: Command-line usage -- Chapter 10: Advanced Routing Configuration -- Chapter 11 High Availability Configuration -- Appendix A: UNIX Basics -- Appendix B: Additional Nokia Packages.
Keywords: Computer networks -- Security measures; Electronic books